Optimization Of Dental and Mouth Health Support at RSAL F.X. Soehardjo for IX Floor Soldiers to Support Operation and Training Activities in Order to Support the Task of The TNI AL - Ruli Yusman; Achmad Faisol (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
With regard to welfare, Law number 34 of 2004 more specifically explains that both soldiers and student soldiers have the right to health care, health and life insurance in Article 50. Good human resources will make soldiers more professional. One of the efforts to achieve this is the professionalism of soldiers is to improve the health of personnel through the implementation of health service management. Dental and oral health support is one of the health supports for the operation and exercise. The implementation of the dental and oral health support program is an inseparable part of the Indonesian Navy's health management, which focuses on efforts to improve health (promotive), healing (curative), and health restoration (rehabilitative) that are comprehensive, integrated, and sustainable. The method used in this paper is a descriptive method using a comprehensive deductive analysis. The writing of this manuscript uses a literature study approach and empirical experience gained while in service. In order to optimize dental and oral health support, steps are taken in the form of increasing dental and oral health personnel by increasing the quantity through increased recruitment, equal distribution of placements in all Indonesian Navy bases, especially in Lantamal IX, and increasing expertise and skills through courses and training. The improvement of dental and oral health facilities is carried out by establishing dental and oral health facilities equipped with mobile dental clinic units and field dental chair units, as well as containers of dental materials and medicines, and the medical technical development of dental care is carried out by carrying out research and development in the field of dentistry. carry out military dentistry training in the marine dimension, and apply teaching materials for military dentistry in Indonesian dentist education.